E-book selection practises and initiatives planning towards return on investment in Malaysian academic libraries: moving into patron-driven acquisition / Che Zainab Abdullah - Abdullah, Che Zainab (2014)
This study investigates the e-book selection practices pertaining to patron-driven acquisition and library’s initiatives planning on providing e-book services toward return on investment in selected Malaysian academic libraries. This research employs a concurrent mixed-method through semi structured interviews and a survey. Ten experienced acquisition librarians informed in this interview. The qualitative data were transcribed and analysed manually. The common purchasing models of e-book in Malaysian academic libraries are subscription, packages, pick and choose and onetime purchase. None of the libraries adopts the patron-driven acquisition model as being investigated. The questionnaire used as an instrument in a quantitative approached to determine librarian perception on common e-book selection practices (resource sharing, accessibility, support distance education, sustainability, collection features, cataloguing e-structure and user friendliness) and library initiatives planning (technical support, personnel and training). The relationship between e-book selection practices, library initiatives planning and return on investment was further examined. Using stratified sampling, questionnaires were distributed to 150 librarians who are handling e-book in either acquisition, automation or reference department. The statistical analyses include descriptive statistics, independent-samples t-test, the oneway analysis of variance (ANOVA), Pearson’s coefficient of correlation and Simple Regression analysis. The various analyses were undertaken using SPSS. The findings indicate that the collection feature of e-book selection practices is perceived by the librarians involved in the study as being relatively the most dominant dimension. This is followed by technical support, a dimension of library initiative planning. Fourteen dimensions (of e-book selection practices, library initiative planning and return on investment) are perceived to be important. The accessibility and training are perceived to be moderately important. Six dimensions of e-book selection practices (accessibility, support distance education, sustainability, collection features, cataloguing e-structure and user friendliness) are positively correlated in varying strengths with return on investment. Three dimensions of library initiatives planning are positively correlated with return on investment. Female respondents had better perceptions on resource sharing and support distance education than male respondents; respondents in the youngest age group (21-29 years) had a poorer perception on collection features and user friendliness than those firom the other two age groups; perceptions on e-book selection practices are the same regardless of respondents’ grades, levels of education and lengths of service. Methodologically, the research illustrates the effective use of the mixed-method approach within the pragmatic research paradigm. The findings of the study are useful for the top management of libraries to realise that purchasing e-book would consequently contribute to the library’s return on investment (librarian’s time saving, cost saving, job commitment and increase in quality). The insight thus gives a better understanding of e-book selection practices within the context of Malaysian academic libraries.